Muscle fibre type composition, motoneuron firing properties, axonal conduction velocity and refractory period for foot extensor motor units in dystrophia myotonica. - Borg, J (1987)
Seven patients with dystrophia myotonica were investigated using neurophysiological combined with histochemical techniques to elucidate motor unit properties in foot extensor muscles, which are often involved in the early stages of this disorder. For the 25 extensor digitorum brevis motor units studied the axonal conduction velocity, the axonal refractory period and the voluntary firing properties were within normal limits. However, high threshold motor units were not observed and the mean value of the axonal conduction velocities was lower (p less than 0.02) for the dystrophia myotonica motor units when compared with corresponding data from healthy subjects. There were also signs of impaired impulse propagation in the terminal part of the motor unit. In muscle biopsy specimens from the anterior tibial muscle, fibre type composition and structure were demonstrated using enzyme histochemical techniques for adenosine-triphosphate and immunohistochemical techniques for identification of the types of myosin isoform present. The histochemical findings indicated a type I fibre dominance, which was most obvious in the more seriously affected muscles. Neonatal myosin was observed preferentially in small but also in some normal sized fibres. Furthermore, some ring fibres were present and these showed staining with antineonatal myosin in their superficial portion. This indicates that an abnormal regeneration is one cause of the myopathic appearance of the muscle fibres in dystrophia myotonica. These investigations show that there is a reduced proportion of type II motor units in foot extensor muscles involved in the myopathy in dystrophia myotonica although it cannot definitely be established whether this is due to a loss of high threshold type II motor units or type II to type I transformation.